2011
DOI: 10.1111/j.1755-5922.2011.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine in Preventing Contrast‐Induced Nephropathy Assessed by Cystatin C

Abstract: SUMMARYAims: Prophylactic oral N-acetylcysteine (NAC) has been widely used for prevention of contrast-induced nephropathy (CIN). However, clinical studies have not been demonstrating this effect consistently because of evidence that NAC can alter serum creatinine levels without affecting glomerular filtration rate (GFR). We investigated NAC for the prevention of CIN by monitoring creatinine and cystatin C. Methods: We enrolled 113 patients (49 patients in NAC group and 64 patients in control group) with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…[ 12 25 ] Supported our results but in rate Abdelrahman et al . [ 26 ] Disagree with our results Nigwekar and Kandula[ 27 ] and Alioglu et al .,[ 28 ] small dose of NAC used in their studies can explain this results. Cystatin C is a low molecular weight protein produced at a constant rate by all nucleated cells.…”
Section: Discussionmentioning
confidence: 91%
“…[ 12 25 ] Supported our results but in rate Abdelrahman et al . [ 26 ] Disagree with our results Nigwekar and Kandula[ 27 ] and Alioglu et al .,[ 28 ] small dose of NAC used in their studies can explain this results. Cystatin C is a low molecular weight protein produced at a constant rate by all nucleated cells.…”
Section: Discussionmentioning
confidence: 91%
“…One might argue that creatinine may not be a sensitive index of glomerular filtration rate (GFR) alterations [ 31 ]. Previous studies suggested that creatinine metabolism can be affected by Nac, so that the observed changes in serum creatinine concentration after administration of Nac may not be indicative of GFR improvement [ 32 ]. In order to overcome these obstacles we assessed sCysC concentration, which can serve as an endogenous marker of renal function and is believed to be superior to plasma creatinine concentration as it does not depend on age, sex and muscle mass, and so it has been considered as a simple, reliable and accurate marker of renal function [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, unlike other experimental studies, novel acute kidney injury marker cystatin C was used to diagnose CIN. Cystatin C is a reliable marker for early diagnosis and prognosis of contrast- induced acute kidney injury in humans (14, 15). Consequently, the present study showed that cystatin C is a sensitive parameter for detecting acute renal injury in rats due to contrast.…”
Section: Discussionmentioning
confidence: 99%